INTEGRATED MARKETING COMMUNICATION AND COFFEE SHOP CONSUMER PURCHASE DECISION IN SURAKARA CITY - Rivandi, Rachman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Integrated Marketing Communication is one of the new generation marketing approaches used by companies to focus their efforts more on acquiring, maintaining and developing relationships with customers and other stakeholders. The purpose of this study was to determine whether there is an effect of Integrated Marketing Communication on the stages of coffee shop consumer purchasing decisions in Surakara City. The population of this research is the people in Surakara who have done transactions at the